Language, Culture and the Neurobiology of Pain: A Theoretical Exploration - Horacio Fabrega (Behavioural Neurology)
Language and culture, as conceptualized in traditional anthropology, may have an important influence on pain and brain-behavior relations. The paradigm case for the influence of language and culture on perception and cognition is stipulated in the Sapir–Whorf hypothesis which has been applied to phenomena “external” to the individual. In this paper, the paradigm is applied to information the person retrieves from “inside” his body; namely, “noxious” stimuli which get registered in consciousness as pain.